The importance of physician to physician coaching, medical director and staff engagement and doing “one thing different” - Ghazala Sharieff (The Beryl Institute, 2019)
With the Center for Medicare and Medicaid Services incorporating patient experience into the Value Based Purchasing metrics, there is increasing hospital focus on improving this important aspect of patient care. The Value Based Purchasing program bases 25% of its value on the patient experience domain and is based on patient perspective as gathered via the Healthcare Consumer Assessment of Healthcare Providers and Systems survey (HCAHPS). Our system chose to implement simultaneous pilot activities to train our 6 Hospitalist groups, obtain Hospitalist medical director buy in and deliver timely physician group feedback in a transparent manner. In addition, a single hospital was used as a pilot site to establish behavioral expectations and empower our front line staff with an innovative “One Thing Different” campaign. Varying results were seen by our different Hospitalist groups and while the group training was the same, it was the level of engagement of the Hospitalist medical director that made a significant difference in the results. Hospitalist group A went from 31st percentile to a current score of 70th percentile; Hospitalist Group B improved from 21st percentile to 63th percentile; Hospitalist group D went from 15th to 31st percentile. Hospitalist Group C improved from 3rd percentile to 25th percentile in just 6 months of project initiation. For the hospital pilot, the average monthly overall rate the hospital score increased from a starting score of 69.2% to 73.96% with the final FY 17 month reaching 77.5%. Currently, the overall rate the hospital score has sustained and is at 73.9%.